Modelling Distributed Cognition Systems in PVS - Masci, Paolo; Curzon, Paul; Blandford, Ann; Furniss, Dominic (Electronic Communications of the EASST, 2011)
We report on our efforts to formalise DiCoT, an informal structured approach for analysing complex work systems, such as hospital and day care units, as distributed cognition systems. We focus on DiCoT's information flow model, which describes how information is transformed and propagated in the system. Our contribution is a set of generic models for the specification and verification system PVS. The developed models can be directly mapped to the informal descriptions adopted by human-computer interactions experts. The models can be verified against properties of interest in the PVS theorem prover. Also, the same models can be simulated, thus facilitating analysts to engage with stakeholders when checking the correctness of the model. We trial our ideas on a case study based on a real-world medical system.